Implementasi Metode Game dalam Pembelajaran Fiqih untuk Meningkatkan Keaktifan Belajar Peserta Didik - Azizah Azizah; Sumanta Sumanta; Moh Ali (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2026)
Fiqh learning in Junior High Schools (SMP) often faces challenges related to low student engagement due to the dominance of lecture based and one way instructional approaches. This study aims to describe the implementation of game based methods in Fiqh learning and to analyze their impact on improving students’ learning engagement at SMPN 1 Telukjambe Timur. The research employed a qualitative approach with a field based case study design. Data were collected through classroom observations, in depth interviews, and documentation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the implementation of game based methods such as Card Sort, Teams Games Tournament (TGT), Wordwall, and Quizizz significantly enhances students’ active participation in cognitive, affective, and psychomotor domains. Supporting factors include teacher readiness, availability of digital facilities, and students’ enthusiasm, while challenges involve limited instructional time and varying academic abilities among students. This study recommends game-based methods as a strategic alternative in Fiqh instruction at Junior High schools to create more interactive, contextual, and meaningful learning experiences.